Morphological Divergence of Snow Trout (Schizothorax Richardsonii, Gray 1932) from Rivers of Nepal with Insights from a Morphometric Analysis - Wagle, Suresh Kumar; Pradhan, Neeta; Shrestha, Madhav Kumar (International Journal of Applied Sciences and Biotechnology, 2015)
Asala or snow trout (Schizothorax richardsonii, Cyprinidae), one of highly valued freshwater fish of Transhimalayan regions, is distributed in upper reaches of all major river systems of Nepal. Morphometric diversification between six river populations of S. richardsonii was examined to identify intraspecific unit for enabling better management of the resources. Significant differences were observed in 17 measured morphometric characters of 207 specimens among the six river populations. Multivariate analysis of variance (Wilks' test) indicated a significant difference for mean vectors of mophometric measurements (? =0.012, F85, 731 = 19.999, P<0.0001) among populations. Principal component and discriminant functions (DFs) analysis of morphometric measurements revealed high seperation of the stocks. The analysis showed that most of the shape and size variation among these populations occurs in the head region, body depth and fin length. Apparent morphometric divergence among S. richardsonii samples showed the existence of three differentiated groups viz., the Indrawati and Khudi populations, the Melamchi and Phalaku Rivers, and the Sabha and Tadi River populations of Nepal. The results of this study may be useful in fisheries management and potential exploitation of this species in coldwater aquaculture. Int J Appl Sci Biotechnol, Vol 3(3): 464-473